Hafnium-based adsorption material, preparation method thereof and method for removing thorium ions in nuclear waste liquid

By using MOF materials composed of hafnium ions and ellagic acid, the problem of poor adsorption of existing MOFs on thorium ions under low pH conditions was solved, and the effect of effectively removing thorium ions in nuclear waste liquid was achieved, and preparation Simple method and low cost.

CN119259006APending Publication Date: 2025-01-07CHINA INSTITUTE OF ATOMIC ENERGY

Patent Information

Application Number
CN202411595579.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing metal organic frame (MOF) materials have poor adsorption effect on thorium ions under low pH conditions, making it difficult to effectively remove thorium ions in nuclear waste liquid treatment.

Method used

Using MOF materials with hafnium ions as metal centers and ellagic acid as organic ligands, a hafnium-based adsorption material with improved adsorption properties is formed through a specific preparation method, including mixing hafnium salts, ellagic acid, organic solvents, water and acetic acid. , a heating reaction is carried out to form a MOF material, and the molar ratio, concentration and reaction conditions are optimized to improve adsorption performance.

Benefits of technology

Under low pH conditions, the adsorption performance of thorium ions can be significantly improved, and the thorium ions in nuclear waste liquid can be effectively removed. The preparation method is simple and the cost is low. The material has a high atomic number metal center and a multi-oxygen functional group, which enhances the Electrostatic adsorption effect on thorium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259006A_ABST
    Figure CN119259006A_ABST
Patent Text Reader

Abstract

The invention provides a hafnium-based adsorption material, a preparation method thereof and a method for removing thorium ions in nuclear waste liquid. The hafnium-based adsorption material comprises an MOF with hafnium ions as a metal center and ellagic acid as an organic ligand, and in an X-ray diffraction pattern of the MOF under CuK alpha radiation, at 5 degrees lt; 2 [theta] lt; and in the range of 20 degrees, four diffraction peaks at the positions of 5.0 degrees + / -0.3 degrees, 8.6 degrees + / -0.3 degrees, 13.2 degrees + / -0.3 degrees and 17.2 degrees + / -0.3 degrees exist. The hafnium-based adsorption material disclosed by the invention has improved adsorption capacity on thorium ions under the condition of low pH value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of radioactive waste liquid treatment, and in particular to a hafnium-based adsorption material, a preparation method thereof, and a method for removing thorium ions from nuclear waste liquid. Background Art

[0002] As a low-carbon clean energy, nuclear energy is regarded by many countries as the preferred way to solve the problem of energy shortage. In the nuclear fuel cycle, radioactive wastewater with different degrees of contamination will be produced in each link of the whole process from uranium mining, smelting, fuel element production and manufacturing, application and spent fuel reprocessing. In the primary loop of nuclear facility operation and the reprocessing of spent fuel, a large amount of waste liquid containing radioactive thorium (Th(IV)) ions will be produced. Th(IV) is radioactive, carcinogenic and toxic, which will cause serious and irreversible damage to the environment and organisms and needs to be removed as a priority. In addition, Th(IV) is a potential nuclear energy resource and is likely to replace the increasingly scarce uranium resources and become the main fuel for future nuclear reactors. Therefore, separating Th(IV) from high-level waste liquid or other wastewater containing Th(IV) can not only reduce the pollution caused by Th(IV) to the environment, but also recycle this precious nuclear energy resource.

[0003] In the related technologies, the main treatment methods for Th(Ⅳ)-containing nuclear wastewater include chemical precipitation, ion exchange, adsorption, liquid-liquid extraction, etc. In the adsorption method, compared with other conventional adsorbents, metal organic framework (MOF) materials have the advantages of high porosity and adjustable pore size, high specific surface area, special metal center, good thermal stability, and easy functionalization, making this type of material a potential material for radioactive nuclide adsorption. However, the existing MOF materials are still obviously insufficient in the capacity of adsorbing Th(Ⅳ).

[0004] Therefore, it is necessary to provide an improved adsorption material. Summary of the invention

[0005] In view of this, the main purpose of the present disclosure is to provide a hafnium-based adsorption material and a preparation method thereof, and a method for removing thorium ions from nuclear waste liquid. The hafnium-based adsorption material has improved adsorption performance for thorium ions under low pH conditions.

[0006] The first aspect of the present disclosure provides a hafnium-based adsorption material, including a MOF with hafnium ions as metal centers and ellagic acid as organic ligands, wherein in the X-ray diffraction pattern of the MOF under CuKα radiation, there are four peaks of diffraction peaks at 5.0°±0.3°, 8.6°±0.3°, 13.2°±0.3°, and 17.2°±0.3° in the range of 5°<2θ<20°. The hafnium-based adsorption material of the present application is a MOF material that can have improved adsorption performance for thorium ions under low pH conditions.

[0007] The second aspect of the present disclosure provides a method for preparing an adsorbent material, comprising: mixing a hafnium salt, ellagic acid, an organic solvent, water and acetic acid to form a precursor solution; and heating the precursor solution to react to obtain a hafnium-based adsorbent material. The preparation method has simple steps, low pollution and low cost. The prepared MOF material has both hafnium metal clusters with high atomic number metal centers and ellagic acid, an organic ligand with multiple oxygen-containing functional groups, and thus can have improved adsorption performance for thorium ions under low pH conditions.

[0008] According to one embodiment of the present disclosure, the molar ratio of the ellagic acid to the hafnium element in the hafnium salt is (1-3):1. This is more conducive to improving the crystallinity of the formed material and forming an optimized crystal structure. Preferably, the molar ratio of the ellagic acid to the hafnium element in the hafnium salt is (1.9-2.1):1.

[0009] According to an embodiment of the present disclosure, in the precursor solution, the concentration of ellagic acid is 0.02mol / L to 0.05mol / L. This is conducive to improving the efficiency of the chemical reaction. Preferably, in the precursor solution, the concentration of ellagic acid is 0.035mol / L to 0.045mol / L.

[0010] According to an embodiment of the present disclosure, in the precursor solution, the concentration of the acetic acid is 4 mol / L to 8 mol / L. This is beneficial for catalyzing the chemical reaction and forming an optimized crystal structure. Preferably, in the precursor solution, the concentration of the acetic acid is 5 mol / L to 7 mol / L.

[0011] According to an embodiment of the present disclosure, the organic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile and methanol. This is conducive to forming an optimized crystal structure. Preferably, the organic solvent is N,N-dimethylformamide.

[0012] According to one embodiment of the present disclosure, in the precursor solution, the volume ratio of the organic solvent to the water is (1-3):1. This is conducive to making the polarity of the solution system reach a range that promotes material formation. Preferably, in the precursor solution, the volume ratio of the organic solvent to the water is (1.5-2.5):1.

[0013] According to an embodiment of the present disclosure, the metal hafnium salt is selected from one or more of hafnium oxychloride and its hydrate, and hafnium tetrachloride. Preferably, the metal hafnium salt is selected from n-hydrate of hafnium oxychloride, where n is an integer of 1 to 8.

[0014] According to one embodiment of the present disclosure, the reaction temperature is 130°C to 180°C. This is conducive to improving the reaction efficiency. Preferably, the reaction temperature is 140°C to 150°C.

[0015] According to an embodiment of the present disclosure, the reaction time is 6 hours to 10 hours. This is conducive to improving the reaction efficiency. Preferably, the reaction time is 7 hours to 9 hours.

[0016] According to one embodiment of the present disclosure, the mixing includes an ultrasonic step, which is conducive to forming a uniform precursor solution.

[0017] A second aspect of the present disclosure provides a method for removing thorium ions from nuclear waste liquid, comprising: adsorbing thorium ions in the nuclear waste liquid by using the above-mentioned hafnium-based adsorption material or the hafnium-based adsorption material obtained according to the above-mentioned preparation method, and removing the adsorption material adsorbing the thorium ions.

[0018] According to one embodiment of the present disclosure, the pH of the nuclear waste liquid is 1-3.

[0019] According to an embodiment of the present disclosure, the concentration of thorium ions in the nuclear waste liquid is 15 mg / L to 300 mg / L, which is conducive to achieving a good effect of adsorbing thorium ions.

[0020] The hafnium-based adsorption material obtained by the preparation method disclosed in the present invention is a MOF material. In the metal-organic framework structure, the oxygen-containing functional groups in the ellagic acid structure can serve as adsorption sites for thorium ions, and the hafnium as the metal center is a metal with a high atomic number, which acts on ellagic acid, further enhancing the electrostatic effect of the MOF structure on thorium ions, thereby being able to have improved adsorption performance for thorium ions under low pH conditions.

[0021] In addition to the technical problems solved by the present disclosure, the technical features that constitute the technical solutions, and the beneficial effects brought about by the technical features of the technical solutions described above, other technical problems that can be solved by the present disclosure, other technical features included in the technical solutions, and the beneficial effects brought about by these technical features will be further described in detail in the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1This is an X-ray crystal diffraction pattern of the hafnium-based adsorption material of Example 1 of the present disclosure.

[0024] Figure 2 It is the X-ray crystal diffraction pattern of the adsorbent material of Comparative Example 1 of the present disclosure.

[0025] Figure 3 1 is a graph showing the relationship between the adsorption capacity of thorium ions and the thorium ion concentration of the hafnium-based adsorption material of Example 1 of the present disclosure.

[0026] Figure 4 1 is an X-ray crystal diffraction diagram of the hafnium-based adsorption material of Example 1 of the present disclosure after being treated with solutions of pH=1, 2, and 3 for 24 hours. DETAILED DESCRIPTION

[0027] The technical solution of the present disclosure will be clearly and completely described below in conjunction with specific implementations and drawings. Obviously, the described implementations are only part of the implementations of the present disclosure, not all of the implementations. Based on the implementations in the present disclosure, all other implementations obtained by ordinary technicians in the field without creative work are within the scope of protection of this application.

[0028] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. In the event of a conflict, this specification takes precedence.

[0029] It should be noted that in the present disclosure, the term "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "comprising..." does not exclude the presence of other related elements in the method or device including the element.

[0030] Note that the phrase "and / or" when used in a list is meant to include alternative embodiments, including each individual component in the list and any combination of components. For example, the list "A, B, and / or C" is meant to include seven independent embodiments, including A, or B, or C, or A+B, or A+C, or B+C, or A+B+C.

[0031] The above steps are divided only for clear description. When implemented, they can be combined into one step or some steps can be split and decomposed into multiple steps. As long as they include the same logical relationship, they are all within the protection scope of this patent.

[0032] Definition of terms

[0033] As used herein, the term "MOF" material refers to a metal-organic framework material, which is a new type of porous crystalline material assembled by coordination of metal ions or metal clusters and bridging organic ligands, with an open framework structure and potential pores. Examples of MOF include, but are not limited to, 2-methylimidazole zinc salt (ZIF-8), MIL-101, UiO-66, and the like.

[0034] The nuclear industry produces a large amount of waste liquid containing radioactive Th(IV). In the related technology of MOF adsorption to remove Th(IV), most of the MOFs studied have adsorption effects under high pH conditions, but the adsorption performance under low pH conditions (pH = 1 to 3) is not ideal. The actual spent fuel reprocessing environment is usually a low pH condition with a pH below 3. Thorium is present in the form of thorium ions Th. 4+ Therefore, a material with good acid stability at low pH and good adsorption capacity for thorium ions is required.

[0035] Svensson et al. (Svensson Grape, et al. "Removal of pharmaceutical pollutants from effluent by a plant-based metal-organic framework." Nature Water 1, 433-442 (2023)) synthesized a MOF material, denoted as SU-102 (Zr), by coordinating zirconium ions with ellagic acid, which can effectively adsorb organic pollutants in wastewater, but has almost no adsorption of radioactive Th (IV) in nuclear waste liquid. Venkata Sravani et al. (Sravani, V. Venkata, et al. "Highly efficient functionalized MOF-LIC-1 for extraction of U (VI) and Th (IV) from aqueous solution: experimental and theoretical studies." Dalton Transactions 51 (2022)) synthesized a group of MOFs, among which the saturated adsorption amount of MOF-LIC-SA for Th (IV) at pH = 6 was 149 mg / g, but it had almost no adsorption under low pH conditions (1-3).

[0036] Because the MOFs adsorbents provided by the prior art have poor adsorption effects on Th(IV) ions under low pH conditions, it is very necessary to develop a MOF adsorbent that can effectively adsorb radioactive nuclides Th(IV) at low pH values.

[0037] Based on this, the present application provides a hafnium-based adsorption material and a preparation method thereof, and a method for removing thorium ions from nuclear waste liquid. The present application and optional implementation methods are described in more detail below.

[0038] Hafnium-based adsorption materials

[0039] In a first aspect, the present application provides a hafnium-based adsorption material, including a MOF with hafnium ions as the metal center and ellagic acid as the organic ligand, wherein in the X-ray diffraction pattern of the MOF under CuKα radiation, there are four peaks of diffraction peaks at 5.0°±0.3°, 8.6°±0.3°, 13.2°±0.3°, and 17.2°±0.3° in the range of 5°<2θ<20°. The hafnium-based adsorption material of the present application is a MOF material, in which the oxygen-containing functional groups in the ellagic acid structure can serve as adsorption sites for thorium ions, and the hafnium as the metal center is a metal with a high atomic number, which acts on ellagic acid, further enhancing the electrostatic effect of the MOF structure on thorium ions, thereby being able to have improved adsorption performance for thorium ions under low pH conditions.

[0040] The hafnium ions and their contents in the hafnium-based adsorption materials mentioned in the present application can be measured using instruments and methods known in the art. For example, EDX-mapping can detect the hafnium element and its content, or after the material is dissolved, it can be tested by inductively coupled plasma atomic emission spectrometry or mass spectrometry, such as Agilent 7850ICP-MS.

[0041] The ellagic acid in the hafnium-based adsorption material mentioned in the present application can be measured by instruments and methods known in the art. For example, the crystal structure can be detected by PXRD to verify whether the synthesis of the material is successful, and the XPS technology can detect the bonding type.

[0042] In some embodiments, the hafnium-based adsorption material of the present application has the following Figure 1 X-ray crystal diffraction pattern shown.

[0043] Preparation method of hafnium-based adsorption material

[0044] The second aspect of the present application provides a method for preparing a hafnium-based adsorption material, which comprises: mixing a hafnium salt, ellagic acid, an organic solvent, water and acetic acid to form a precursor solution; and heating the precursor solution to react to obtain the hafnium-based adsorption material.

[0045] The preparation method of the hafnium-based adsorption material of the present application has simple steps. Acetic acid is used as a catalyst, water is used as a high-polarity agent for adjusting the polarity of the reaction system, and an organic solvent is used as a template agent. The obtained high-polarity system is conducive to the synthesis of the hafnium-based adsorption material disclosed in the present application. The organic ligand adopts natural polyphenols (i.e., ellagic acid), which has little pollution and low cost. And combined with hafnium ions, an MOF material is formed. Since the material has both hafnium metal clusters with high atomic number metal centers and ellagic acid, an organic ligand with multiple oxygen-containing functional groups, it can have improved adsorption performance for thorium ions under low pH conditions.

[0046] In some embodiments, the molar ratio of the ellagic acid to the hafnium element in the hafnium salt is (1-3):1; thus, it is more conducive to improving the crystallinity of the formed material and forming an optimized crystal structure.

[0047] Exemplarily, the molar ratio of ellagic acid to the hafnium element in the hafnium salt is 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or a value within a range consisting of any two values. Preferably, the molar ratio of ellagic acid to the hafnium element in the hafnium salt is (1.9-2.1):1.

[0048] In some embodiments, in the precursor solution, the concentration of ellagic acid is 0.02 mol / L to 0.05 mol / L, which is beneficial to improve the efficiency of the chemical reaction.

[0049] Exemplarily, in the precursor solution, the concentration of ellagic acid is 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L or a value in the range of any two values. Preferably, the concentration of ellagic acid is 0.035 mol / L to 0.045 mol / L.

[0050] In some embodiments, the concentration of acetic acid in the precursor solution is 4 mol / L to 8 mol / L, which is beneficial for catalyzing the chemical reaction and forming an optimized crystal structure.

[0051] Exemplarily, in the precursor solution, the concentration of acetic acid is 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L or a value in a range consisting of any two values. Preferably, in the precursor solution, the concentration of acetic acid is 5 mol / L to 7 mol / L.

[0052] In some embodiments, the organic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile, and methanol. This is conducive to forming an optimized crystal structure. Preferably, the organic solvent is N,N-dimethylformamide.

[0053] In some embodiments, in the precursor solution, the volume ratio of the organic solvent to the water is (1-3): 1. This is conducive to making the polarity of the solution system reach a range that promotes material formation.

[0054] Exemplarily, the volume ratio of the organic solvent to the water is 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or a value within a range consisting of any two values. Preferably, in the precursor solution, the volume ratio of the organic solvent to the water is (1.5-2.5):1.

[0055] In some embodiments, the metal hafnium salt is selected from one or more of hafnium oxychloride and its hydrate, and hafnium tetrachloride. Preferably, the metal hafnium salt is selected from n-hydrate of hafnium oxychloride, where n is an integer of 1 to 8.

[0056] In some embodiments, the mixing includes an ultrasonic step, which is conducive to forming a uniform precursor solution.

[0057] In some embodiments, the reaction temperature is 130°C to 180°C. This is conducive to improving the reaction efficiency. Exemplarily, the reaction temperature is 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a value within a range consisting of any two values. Preferably, the reaction temperature is 140°C to 150°C.

[0058] In some embodiments, the reaction time is 6 h to 10 h. This is conducive to improving the reaction efficiency. Exemplarily, the reaction temperature is 6 h, 7 h, 8 h, 9 h, 10 h or a value within the range of any two values. Preferably, the reaction time is 7 h to 9 h.

[0059] Method for removing thorium ions from nuclear waste liquid

[0060] The embodiment of the present application also provides a method for removing thorium ions from nuclear waste liquid. The method comprises: using the hafnium-based adsorbent material according to the present disclosure or the hafnium-based adsorbent material prepared according to the method of the present disclosure, adsorbing the thorium ions in the nuclear waste liquid, and removing the adsorbent material adsorbing the thorium ions. Therefore, it has at least the same advantages as the hafnium-based adsorbent material.

[0061] In some embodiments, the pH of the nuclear waste liquid is 1 to 3. Exemplarily, the pH of the nuclear waste liquid is 1, 1.5, 2.0, 2.5, 3.0, or a value within a range consisting of any two values.

[0062] In some embodiments, the concentration of thorium ions in the nuclear waste liquid is 15 mg / L to 300 mg / L. This is conducive to achieving a good adsorption effect of thorium ions. Exemplarily, the concentration of thorium ions in the nuclear waste liquid is 15 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, or a value within a range consisting of any two values.

[0063] Experimental Materials:

[0064] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0065] X-ray crystal diffraction was performed by an X-ray crystal diffractometer (manufacturer: Bruker, model D8 QUEST). The sample to be tested was prepared by a flat plate sample preparation method, with CuKα rays as the radiation source, a copper target as the anode target, a voltage of 40 KV, a current of 40 mA, an anti-scattering slit of 1 mm, a scanning 2θ angle range of 20°-80°, a step length of 0.01671°, a step length of 0.24 s, and a scanning rate of 4° / min.

[0066] ICP-MS analysis was performed using an inductively coupled plasma mass spectrometer (Agilent 7850 ICP-MS).

[0067] Example

[0068] Example 1.

[0069] Hafnium (IV) dichloride octahydrate (HfCl2O.8H2O, 2.05 g, 0.005 mol) was added to 100 mL of DMF and mixed evenly by ultrasonication for 20 min; then, ellagic acid (3 g, 0.01 mol), 75 mL of glacial acetic acid, and 50 mL of deionized water were added in sequence, and ultrasonication was continued for 5 min to obtain a precursor solution, wherein the molar ratio of ellagic acid to the hafnium element in hafnium dichloride octahydrate was 2:1, and in the precursor solution, the concentration of ellagic acid was 0.044 mol / L, the concentration of acetic acid was 5.8 mol / L, and the volume ratio of DMF to ethanol was 2:1.

[0070] The precursor solution was transferred to a flask equipped with a condenser and heated with stirring at 140° C. for 8 hours in air. After the reaction was completed, the reactor was gradually cooled to room temperature and the solid was collected by centrifugation.

[0071] The collected solid was dispersed in 50 mL of DMF, stirred at room temperature for 12 h and filtered; this was repeated three times to remove impurities and unreacted raw materials. The same operation was repeated using 50 mL of deionized water instead of DMF to remove DMF.

[0072] Finally, it was dried at 130 °C overnight to obtain the hafnium-based adsorption material.

[0073] Comparative Example 1.

[0074] The adsorbent material was prepared in the same manner as in Example 1, except that zirconium (IV) oxychloride octahydrate (0.005 mol) was used instead of hafnium (IV) oxychloride octahydrate (2.05 g, 0.005 mol). The prepared material corresponds to the adsorbent material SU-102 (Zr) in the related art (Svensson Grape, et al. "Removal of pharmaceutical pollutants from effluent bya plant-based metal-organic framework." Nature Water 1, 433-442 (2023)).

[0075] X-ray crystal diffraction analysis was performed on the adsorbent materials of Example 1 and Comparative Example 1. The results are as follows: Figure 1 and Figure 2 It can be seen that the adsorbent material obtained in Example 1 of the present application has four diffraction peaks with higher intensity at 5.0°, 8.6°, 13.2°, and 17.2° in the range of 5°<2θ<20°. The MOF material SU-102 of Comparative Example 1 has a diffraction peak of 1.0°, 1.2°, and 2.0°.

[0076] (Zr) also has a peak with similar intensity and shape, which indicates that Example 1 prepared a similar SU-102

[0077] (Zr) MOF structure.

[0078] Comparative Example 2.

[0079] The adsorption material was prepared in the same manner as in Example 1, except that 50 mL of ethanol was used instead of 50 mL of deionized water.

[0080] Performance Testing

[0081] 1. Test of adsorption capacity of thorium ions at different pH

[0082] (1) Prepare 45 mL of thorium nitrate tetrahydrate solution with an initial thorium ion concentration of approximately 250 mg / L. Divide the solution into three equal portions, each with 15 mL. Adjust the solution with 0.01 M nitric acid to obtain thorium ion solutions with pH values ​​of 1, 2, and 3, respectively. Measure the precise concentration of thorium ions before adsorption, C0, by ICP-MS.

[0083] (2) Take the above three portions of thorium ion solution, each with a volume of V = 10 mL, and add a mass of m = 2 × 10 -3 The MOF sample of 1 g was shaken at 25 °C for 5 h to remove the adsorbent material adsorbed with thorium ions.

[0084] (3) Take the supernatant and measure the residual thorium ion concentration C in the solution by ICP-MS i , the adsorption capacity Q was calculated according to the following formula, and the results are shown in Table 1.

[0085]

[0086] The test results of the adsorption capacity of thorium ions of the adsorbent materials prepared in the above Example 1 and Comparative Examples 1 to 3 at different pH values ​​are shown in Table 1.

[0087] Table 1

[0088]

[0089] It can be seen from the above results that the hafnium-based adsorption material disclosed in the present invention can effectively adsorb ions of the radioactive nuclide Th(IV) under low pH (pH=1 to 3) conditions.

[0090] 2. Test of adsorption capacity of thorium ions at different thorium ion concentrations

[0091] (1) Prepare 5 25 mL thorium nitrate tetrahydrate solutions (with initial thorium ion concentrations of approximately 5, 50, 100, 250, and 300 mg / L, respectively). Adjust the pH of the 5 thorium ion solutions to 3 using 0.01 M nitric acid. Measure the precise concentration of thorium ions before adsorption, C0, by ICP-MS.

[0092] (2) Take 5 portions of the above thorium ion solution, each with a volume of V = 10 mL, and add a mass of m = 2 × 10 -3 The MOF material sample of Example 1 of g was shaken at 25° C. for 5 h to remove the adsorbent material adsorbed with thorium ions.

[0093] (3) Take the supernatant and measure the residual thorium ion concentration C in the solution by ICP-MS i , the adsorption capacity Q is calculated according to the above formula, and the result is as follows Figure 3The adsorption capacity of the MFO material of Example 1 for thorium ions increases with the increase of thorium ion concentration. When the thorium ion concentration is above 250 mg / L, the degree of change in the adsorption capacity is small.

[0094] 3. Chemical stability test

[0095] (1) 20 mL of aqueous solutions with pH values ​​of 1, 2, and 3 were prepared using 0.01 M nitric acid.

[0096] (2) 10 mg of the MOF sample of Example 1 was added to each of the three aqueous solutions. After standing for 24 h, the MOF material was separated by centrifugation and dried at 100° C.

[0097] (3) The dried samples were tested by X-ray crystal diffraction instrument. The results are as follows Figure 4 As shown, four high-intensity diffraction peaks can still be clearly seen at 5.0°, 8.6°, 13.2°, and 17.2° for the three samples, proving that the materials have high chemical stability at low pH values.

[0098] Examples 2-3.

[0099] The adsorption material was prepared in the same manner as in Example 1, except that when preparing the precursor solution, the amount of ellagic acid added was adjusted to change the molar ratio of ellagic acid to the hafnium element in hafnium dichloride octahydrate.

[0100] Table 2 shows the test results of the adsorption capacity of thorium ions of the hafnium-based adsorption materials of Examples 1 to 3 at pH=3.

[0101] Table 2

[0102]

[0103] It can be seen from the above results that when the molar ratio of ellagic acid to the hafnium element in the hafnium salt and the concentration of ellagic acid in the preparation method of the embodiment of the present disclosure are within the above range, the obtained hafnium-based adsorbent material can have an improved adsorption capacity for thorium ions under low pH conditions.

[0104] The above descriptions are only some specific embodiments of the present disclosure, which are intended to illustrate the present disclosure and are not intended to limit the scope of protection claimed in the present application. All modifications, substitutions, or direct / indirect applications made in other related technical fields based on the inventive concept of the present disclosure and using the description of the present application are included in the scope of protection claimed in the present application.

Claims

1. A hafnium-based adsorption material, comprising a MOF with hafnium ions as the metal center and ellagic acid as the organic ligand, wherein in the X-ray diffraction pattern of the MOF under CuKα radiation, there are four diffraction peaks at 5.0°±0.3°, 8.6°±0.3°, 13.2°±0.3°, and 17.2°±0.3° in the range of 5°<2θ<20°.

2. A method for preparing a hafnium-based adsorption material, comprising: mixing a hafnium salt, ellagic acid, an organic solvent, water and acetic acid to form a precursor solution; as well as The precursor solution is heated to react to obtain a hafnium-based adsorption material.

3. The preparation method according to claim 2, wherein The molar ratio of the ellagic acid to the hafnium element in the hafnium salt is (1-3):1; preferably, the molar ratio of the ellagic acid to the hafnium element in the hafnium salt is (1.9-2.1):

1.

4. The preparation method according to claim 2, wherein: In the precursor solution, the concentration of ellagic acid is 0.02 mol / L to 0.05 mol / L; preferably, in the precursor solution, the concentration of ellagic acid is 0.035 mol / L to 0.045 mol / L.

5. The preparation method according to claim 2, wherein: In the precursor solution, the concentration of the acetic acid is 4 mol / L to 8 mol / L; preferably, in the precursor solution, the concentration of the acetic acid is 5 mol / L to 7 mol / L.

6. The preparation method according to claim 2, wherein: The organic solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile, and methanol; preferably, the organic solvent is N,N-dimethylformamide; preferably, in the precursor solution, the volume ratio of the organic solvent to the water is (1-3):1; preferably, in the precursor solution, the volume ratio of the organic solvent to the water is (1.5-2.5):

1.

7. The preparation method according to claim 2, wherein: The metal hafnium salt is selected from one or more of hafnium oxychloride and its hydrate, and hafnium tetrachloride; preferably, the metal hafnium salt is selected from n-hydrate of hafnium oxychloride, where n is an integer of 1 to 8.

8. The preparation method according to claim 2, wherein: The reaction temperature is 130°C to 180°C; preferably, the reaction temperature is 140°C to 150°C; preferably, the reaction time is 6h to 10h; preferably, the reaction time is 7h to 9h; preferably, the mixing includes an ultrasonic step.

9. A method for removing thorium ions from nuclear waste liquid, comprising: Thorium ions in the nuclear waste liquid are adsorbed by using the hafnium-based adsorbent material according to claim 1 or the hafnium-based adsorbent material obtained by the preparation method according to any one of claims 2 to 8, and the adsorbent material adsorbing the thorium ions is removed.

10. The method according to claim 9, wherein: The pH of the nuclear waste liquid is 1 to 3; preferably, the concentration of thorium ions in the nuclear waste liquid is 15 mg / L to 300 mg / L.

Citation Information

Patent Citations

  • Logging machine

    SU1020076A1

Cited By

  • Zirconium-based metal organic framework adsorbing material for recovering gold as well as preparation method and application thereof

    CN121466999A

  • Zirconium-based metal-organic framework adsorbent material for recovering gold and preparation method and application thereof

    CN121466999B